Increased Efficacy of Histone Methyltransferase G9a Inhibitors Against MYCN-Amplified Neuroblastoma - Bellamy, Jacob; Szemes, Marianna; Melegh, Zsombor; Dallosso, Anthony; Kollareddy, Madhu; Catchpoole, Daniel; Malik, Karim (Frontiers in Oncology, 2020)
Targeted inhibition of proteins modulating epigenetic changes is an increasingly important priority in cancer therapeutics, and many small molecule inhibitors are currently being developed. In the case of neuroblastoma (NB), a paediatric solid tumour with a paucity of intragenic mutations, epigenetic deregulation may be especially important. In this study we validate the histone methyltransferase G9a/EHMT2 as being associated with indicators of poor prognosis in NB. Immunological analysis of G9a protein shows it to be more highly expressed in NB cell-lines with MYCN amplification, which is a primary determinant of dismal outcome in NB patients. Furthermore, G9a protein in primary tumours is expressed at higher levels in poorly differentiated/undifferentiated NB, and correlates with high EZH2 expression, a known co-operative oncoprotein in NB. Our functional analyses demonstrate that siRNA-mediated G9a depletion inhibits cell growth in all NB cell lines, but, strikingly, only triggers apoptosis in NB cells with MYCN amplification, suggesting a synthetic lethal relationship between G9a and MYCN. This pattern of sensitivity is also evident when using small molecule inhibitors of G9a, UNC0638 and UNC0642. The increased efficacy of G9a inhibition in the presence of MYCN-overexpression is also demonstrated in the SHEP-21N isogenic model with tet-regulatable MYCN. Finally, using RNA sequencing, we identify several potential tumour suppressor genes that are reactivated by G9a inhibition in NB, including the CLU, FLCN, AMHR2 and AKR1C1-3. Together, our study underlines the under-appreciated role of G9a in NB, especially in MYCN-amplified tumours.